Introduction to oil company financial analysis - Johnston, David, 1950 August 28- (Knovel Library., 2006)
Basic principles are widely understood in the financial industry, but the terminology and analytical techniques can vary greatly. This book is written for the nonfinancial shareholders, managers, and oil company employees interested in the forces that influence stock values. The bottom line in any company is expressed in the language of finance. This book explains financial concepts in a nontechnical, practical way so that nonfinancial professionals and others may understand and appreciate this aspect of the business. When the first edition of this book was written, companies disclosed substantially less information than what is available today. This additional information allows a better understanding of the financial status and health of a company. But there is still room for improvement -- Product Description.